2021
DOI: 10.1002/hyp.14195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the undecomposed layer and semi‐decomposed layer of Quercus variabilis litter on the soil erosion process and the eroded sediment particle size distribution

Abstract: Simulated rainfall experiments were performed on bare, undecomposed litter layer and semi-decomposed litter layer slopes with litter biomasses of 0, 50, 100 and 150 g m À2 , respectively, to evaluate the effect of the undecomposed layer and semidecomposed layer of Quercus variabilis litter on the soil erosion process and the particle size distribution of eroded sediment. The undecomposed layer and semidecomposed layer of litter reduced the runoff rate by 10.91-27.04% and 12.91-36.05%, respectively, and the ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The influence of the specific conditions of a slope with a northern exposure contributes to a decrease in the content of soil organic matter in luvic chernozem compared to luvic chernozem on a slope of southern exposure, which can be explained by the presence of a higher clay content (Zheng et al, 2023). Some researchers have found opposite trends -increased organic matter content in forest soils on a northern slope compared to forest soils on a southern slope (Liu et al, 2021), which can be explained by the characteristics of the soils and forest vegetation that were studied. The results of analysis of variance confirm the significant influence of the features of slope exposures on the content of soil organic matter in luvic chernozems, as well as the reliable influence of forest vegetation on the content of organic matter in chernozems, which can be explained by the protective role of the forest, which protects the soil from degradation (Yakovenko et al, 2024), limiting the loss of soil organic matter (Dong et al, 2022) and the reduction of upper soil horizons (Wiśniewski & Märker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the specific conditions of a slope with a northern exposure contributes to a decrease in the content of soil organic matter in luvic chernozem compared to luvic chernozem on a slope of southern exposure, which can be explained by the presence of a higher clay content (Zheng et al, 2023). Some researchers have found opposite trends -increased organic matter content in forest soils on a northern slope compared to forest soils on a southern slope (Liu et al, 2021), which can be explained by the characteristics of the soils and forest vegetation that were studied. The results of analysis of variance confirm the significant influence of the features of slope exposures on the content of soil organic matter in luvic chernozems, as well as the reliable influence of forest vegetation on the content of organic matter in chernozems, which can be explained by the protective role of the forest, which protects the soil from degradation (Yakovenko et al, 2024), limiting the loss of soil organic matter (Dong et al, 2022) and the reduction of upper soil horizons (Wiśniewski & Märker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The litter layer is one of the three hydrologic layers in the forest ecosystem and is crucial for controlling soil erosion [15]. Liu [16] studied the effects of the undecomposed layer and semi-decomposed layer of Quercus variabilis litter on soil erosion, and found that they reduced the runoff rate by 10.91-27.04% and 12.91-36.05%, respectively. The litter layer can consume the kinetic energy of raindrops, delay the runoff generation time, decrease the impact of the surface soil erosion ratio, reduce soil erosion and improve soil infiltration [17].…”
Section: Introductionmentioning
confidence: 99%